Thalidomide-induced sinus bradycardia in Crohn's disease: case report and literature review. Issue 5 (May 2019) - Liu, Menghui; Lin, Xiaoqing; Wang, Lichun; He, Yao; Chen, Minhu; Mao, Ren
Thalidomide is effective in inducing and maintaining clinical remission, as well as mucosal healing, in patients with refractory Crohn's disease (CD). However, long-term use of thalidomide has raised concern because of the high incidence of adverse events. Cardiovascular events induced by thalidomide have been reported in patients with multiple myeloma, amyotrophic lateral sclerosis, and transfusion-dependent refractory anemia. We report here an extremely rare case of sinus bradycardia induced by thalidomide in an adult patient with CD. This patient's heart rate converted back to a normal sinus rhythm after withdrawal of thalidomide, but recurred after restarting of thalidomide. Cardiac toxicity should be closely monitored when using thalidomide in patients with CD.